The Influence of Parenting Style, Religious Culture of Madrasah, and Self-Regulation on Students' Morality in Private Madrasah Aliyah Schools in Pekanbaru - Ningsih, Wirda; Zein, Mas'ud; Zaitun, Zaitun (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
¬¬¬ ABSTRACTThis study investigates the impact of parenting style, the religious culture of Madrasahs, and self-regulation on the moral character of students in private Madrasah Aliyah institutions in Pekanbaru City. The study utilized a quantitative methodology through a survey technique. The sample comprised 205 students chosen from three Madrasahs with differing accreditation statuses. Data were gathered by questionnaires and documentation, and analyzed with multiple linear regression. The results demonstrate that parenting style significantly influences students' morals, with a significance value of 0.000 (< 0.05) and a contribution of 77.8%. The religious culture of Madrasahs notably affects students' moral behavior, evidenced by a significance value of 0.003 (< 0.05) and a contribution of 4.4%. Simultaneously, self-regulation exerts a substantial influence on students' morals, evidenced by a significance value of 0.000 (< 0.05) and a contribution of 20%. Concurrent analysis indicates that parental style and religious culture collectively account for 78.6% of students' morality, whereas the interplay of religious culture and self-regulation contributes 23%. The three variables; parenting style, religious school culture, and self-regulation collectively exhibit a substantial influence on children' moral character, contributing 99.2% with a significance level of 0.000. These findings underscore the significance of a holistic strategy that incorporates familial, educational, and individual psychological elements in character education. The study provides significant insights for formulating more effective, evidence-based tactics in moral instruction within Islamic educational institutions.